2001
DOI: 10.1093/emboj/20.11.2723
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin is a downstream effector of trafficking PKC-integrin complexes involved in the control of cell motility

Abstract: Protein kinase C (PKC) alpha has been implicated in beta1 integrin-mediated cell migration. Stable expression of PKCalpha is shown here to enhance wound closure. This PKC-driven migratory response directly correlates with increased C-terminal threonine phosphorylation of ezrin/moesin/radixin (ERM) at the wound edge. Both the wound migratory response and ERM phosphorylation are dependent upon the catalytic function of PKC and are susceptible to inhibition by phosphatidylinositol 3-kinase blockade. Upon phorbol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
231
2
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(246 citation statements)
references
References 39 publications
(76 reference statements)
7
231
2
6
Order By: Relevance
“…ERM (ezrin [Ez], radixin [Rdx], moesin [Moe]) family proteins are known to be mediators between cellular scaffold (actin) and membrane structures (14) and by analogy have also been proposed to serve as anchoring proteins for PKC (15). This is in agreement with reports showing an interaction of PKC␣ with ezrin in vivo (24) and with the identification of ERM proteins as anchoring molecules for cyclic AMP-dependent kinase (11).…”
supporting
confidence: 75%
“…ERM (ezrin [Ez], radixin [Rdx], moesin [Moe]) family proteins are known to be mediators between cellular scaffold (actin) and membrane structures (14) and by analogy have also been proposed to serve as anchoring proteins for PKC (15). This is in agreement with reports showing an interaction of PKC␣ with ezrin in vivo (24) and with the identification of ERM proteins as anchoring molecules for cyclic AMP-dependent kinase (11).…”
supporting
confidence: 75%
“…In previous studies, we have shown ezrin to be an important mediator of breast cancer cell migration (Ng et al, 2001) and a number of recent articles have highlighted the significant contribution of ezrin to the clinical development of metastasis in both osteosarcoma and rhabdomyosarcoma Yu et al, 2004;Elliott et al, 2005). Mechanistically, ERM proteins have been implicated in the regulation of the Rho family of small GTPases either through inhibition of the Rho-specific GDP dissociation inhibitor RhoGDI (Takahashi et al, 1997) or through interaction with the Cdc42/Rhospecific guanine exchange factor Dbl (Vanni et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Activation of ERM proteins occurs by conformational changes triggered by binding of phosphatidylinositol 4,5-biphosphate (PIP 2 ) to the FERM (band 4.1, ERM) domain in the NH 2 -terminal region, termed the NH 2 -terminal ERM-associated domain (N-ERMAD) and phosphorylation of a conserved threonine residue (ezrin-T567, radixin-T564, moesin-T558) in the COOH-terminal domain, termed the COOH-terminal ERMassociated domain (C-ERMAD; Pietromonaco et al, 1998;Barret et al, 2000;Ng et al, 2001;Fievet et al, 2004). This sequence of molecular events releases the intramolecular interaction between the N-and C-termini.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since alterations in adhesion forces, cell spreading and membrane tension have been reported as being responsible for defective cell migration [23][24][25][26], we tested the ability of Myo1g-deficient B cells to migrate toward a chemokine gradient. We used CXCL13 to induce migration of resting B lymphocytes over a fibronectincoated surface in a chemotaxis chamber.…”
Section: Slow B-cell Migration In Vitro and Defective Homing In Vivomentioning
confidence: 99%